Climate Change Perception: A Comparative Study of Urban-Rural Communities in District Peshawar, Pakistan - Danish Mujahid; Shah Nawaz Khan; Sardar Muzaffar Hussain Zahid (Journal of Peace, Development and Communication, 2022)
The ecosystem plays a vital role in sustaining life on Earth, whereas, the atmosphere provides the required medium for growth and survival. Severe environmental, economic, and social impacts are expected due to Climate Change (CC) on South Asia in general and people whose livelihoods depend on the use of natural resources in particular. They are likely to bear the burden of its adverse impacts. Among the countries negatively affected by CC, Pakistan is also included due to its high exposure to extreme events and low adaptive capacity. People perception and the knowledge on CC can impact the success of implemented adaptation and mitigation options, it is therefore important for communities to make regular efforts to analyze this information. This study was conducted in district Peshawar. The study was conducted to determine the level of knowledge on CC among respondents, their perceptions on the impacts of CC and measures they are undertaking to tackle its effects. Data were collected through questionnaires and interviews. Respondents were divided into farmers, government employees and students. Knowledge was judged by the ability of the respondents to define the concept of CC. The study designated that the level of knowledge was high. Respondents had detected an increase in temperature along with decrease in precipitation (rainfall) within the district over the last few years. Negative Impact of CC experienced by the respondents on their health is vector-borne diseases. Measures for adaptation of CC such as planting drought-resistant crops, construction of wells, planting trees and sustainable energy through solar panels is adopted by respondents. Although, the results indicate that respondents were not aware of the government adaptation plans on CC. The lack of knowledge about adaptive measures, finance and technical resources is a hurdle for respondents to adopt measures to combat impacts of CC consequences. Based on findings the mass media and the local communities should be involved by the government while designing policies for mitigating the impacts of CC.